Azo-dye-doped absorbing photonic crystals with purely imaginary refractive index contrast and all-optically switchable diffraction properties - Dai, Haitao (2013)
We demonstrate a two-dimensional absorbing photonic crystal with a uniform real part of the refractive index, but a periodically modulated imaginary part. It was realized through back-filling the voids of a periodic array of azo-dye-doped polymeric disks with the same undoped polymers. The photonic crystals were characterized using the diffraction method. The experimental results showed that only the light in the spectral range where the azo-dye absorbed was diffracted, indicating that a purely absorbing photonic crystal was formed. This absorbing photonic crystal also showed switchable diffraction properties due to the trans-cis isomerization of the azo-dye under the light pump.